Chemoprevention of 4NQO-Induced Mouse Tongue Carcinogenesis by AKT Inhibitor through the MMP-9/RhoC Signaling Pathway and Autophagy - Panpan Yin; Jiahui Chen; Yanlin Wu; Feng Gao; Jinlin Wen; Wenbin Zhang; Ying Su; Xinyan Zhang (Analytical Cellular Pathology)
Oral cancer (OC), the most common cancer in the head and neck, which has a poor prognosis, histopathologically follows a stepwise pattern of hyperplasia, dysplasia, and cancer. Blocking the progression of OC in the precancer stage could greatly improve the survival and cure rates. AKT protein plays a critical role in the signal transduction of cancer cells, and we found that AKT was overexpressed in human OC samples through analysis of TCGA database. Therefore, this study is aimed at investigating the chemopreventive effect of an AKT inhibitor (MK2206 2HCl) on OC. In vivo, we established a 4-nitroquinoline-1-oxide- (4NQO-) induced mouse tongue carcinogenesis model to investigate the potential chemopreventive effect of MK2206 2HCl on mouse OC resulting from 4NQO. The results showed that MK2206 2HCl could significantly reduce the incidence rate and growth of OC, inhibit the transformation of dysplasia to cancer in the 4NQO-induced mouse tongue carcinogenesis model, and simultaneously markedly suppress cell proliferation, angiogenesis, and mast cell (MC) infiltration in 4NQO-induced mouse tongue cancers. In vitro, our results revealed that MK2206 2HCl could also inhibit oral squamous cell carcinoma (OSCC) cell malignant biological behaviors, including cell proliferation, colony formation, cell invasion, and migration, while promoting apoptosis. Mechanistic studies revealed that MK2206 2HCl suppressed matrix metalloproteinase 9 (MMP-9) and RhoC expression and promoted autophagy gene LC3 II expression. In summary, our findings demonstrated the chemopreventive effect of MK2206 2HCl on the 4NQO-induced mouse tongue carcinogenesis model, which likely has an underlying mechanism mediated by the MMP-9/RhoC signaling pathway and autophagy.